Analisis Peran Motivasi, Disiplin, dan Learning Agility terhadap Kinerja Operasional Pemadam Kebakaran - Ahmad Faizurohman; Ade Solahudin (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of work motivation, work discipline, and learning agility on the operational performance of firefighters in Cirebon Regency. The research method used was a quantitative explanatory method with a census technique (total sampling) of 160 firefighters spread across 11 Technical Implementation Units (UPT) in Cirebon Regency. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression analysis, the classical assumption test, the coefficient of determination test, the t-test, and the F-test. The results showed that work motivation had a positive and significant effect on operational performance with a regression coefficient of 0.320 and a significance value <0.001. Work discipline had a positive and significant effect with a regression coefficient of 0.913 and a significance value <0.001 and was the most dominant variable. While learning agility had a positive and significant effect with a regression coefficient of 0.208 and a significance value of 0.025. Simultaneously, work motivation, work discipline, and learning agility had a positive and significant effect on operational performance, with an F-value of 252.947 and a significance level of <0.001. The coefficient of determination (R²) of 0.829 indicates that 82.9% of the variation in operational performance can be explained by these three variables. The conclusion of this study is that work motivation, work discipline, and learning agility are important factors in improving the operational performance of firefighters, with work discipline being the most dominant factor.   Keywords: Work Motivation, Work Discipline, Learning Agility, Operational Performance, Firefighters